A new model for analyzing antimicrobial peptides with biomedical applications - Beschin, Alain; Bilej, M. (IOS ; Ohmsha, 2002)
This volume first presents evidence for the earthworm's immune system; the results strongly suggest that certain molecules of the earthworm's immune system may be exploited as natural antibiotics - thus the biomedical applications.
Keywords: Peptide antibiotics -- Congresses.; Earthworms -- Congresses.; Biomedical engineering.; Antimicrobial Cationic Peptides -- analysis; Biomedical Engineering; Annelida -- immunology; Biomedical Technology; Antibiotiques peptidiques -- Congrès.; Génie biomédical.; biomedical engineering.; SCIENCE -- Life Sciences -- Zoology -- Invertebrates.; Peptide antibiotics.; Earthworms.; Biomedical engineering; Earthworms; Peptide antibiotics; Antibactériens.; Invertébrés -- Immunologie -- Congrès.; Congress; proceedings (reports); Conference papers and proceedings; Conference papers and proceedings.; Actes de congrès.